The Impacts of the Turkish Constitutional Court's Individual Application Judgments about the Right to Fair Trial on Criminal Proceedings - Sedat Erdem Aydın (Ceza Hukuku ve Kriminoloji Dergisi)
This paper pursues the purpose of giving insight to researchers and jurists, especially non-Turkish ones, about the progress of the individual application to the Turkish Constitutional Court. The individual application was introduced into the Turkish legal system by the 2010 constitutional amendments, and it started to function on 23 September 2012. Article 148 of the Constitution states that everyone may apply to the Turkish Constitutional Court on the grounds that one of the fundamental rights and freedoms under joint protection of the Constitution and the European Convention on Human Rights has been violated by public authorities, after having exhausted ordinary legal remedies. With the amendments, a new era started in the Turkish law system. First, the official statistics of individual applications published by the Turkish Constitutional Court will be analyzed. Later, Turkish Constitutional Court's individual application judgments about the right to a fair trial, which carries great importance due to having the largest number of judgments of violation given by the Turkish Constitutional Court, will be evaluated. Lastly, views about the impacts of the Turkish Constitutional Court's judgments about the violations of rights on the criminal procedure will be examined.